2018
DOI: 10.1186/s12881-018-0684-8
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen receptor 1 gene affects bone mineral density and osteoporosis treatment efficiency in Slovak postmenopausal women

Abstract: BackgroundThe study investigated the associations of rs9340799:A > G (XbaI) and rs2234693:T > C (PvuII) polymorphisms in the estrogen receptor 1 gene (ESR1) with femoral neck (BMD-FN) and lumbar spine bone mineral density (BMD-LS), biochemical markers of bone turnover, calcium and phosphate levels, fracture prevalence, and a response to two types of anti-osteoporotic therapy in postmenopausal women from southern Slovakia.MethodsWe analysed 343 postmenopausal Slovak women (62.40 ± 0.46 years). The influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
1
20
0
2
Order By: Relevance
“…Additionally, the importance of ERs on cortical and trabecular bone, and also in different bone cell types have been widely explored (42). Although the studied genetic polymorphism rs2234693 and rs9340799 in ESR1 and rs1256049 and rs4986938 were not associated with PAP in the present study, they were previously associated with many different bone conditions (28,43) and oral conditions (43)(44)(45). The genetic polymorphisms rs2234693 and rs9340799 in ESR1 have been largely studied.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Additionally, the importance of ERs on cortical and trabecular bone, and also in different bone cell types have been widely explored (42). Although the studied genetic polymorphism rs2234693 and rs9340799 in ESR1 and rs1256049 and rs4986938 were not associated with PAP in the present study, they were previously associated with many different bone conditions (28,43) and oral conditions (43)(44)(45). The genetic polymorphisms rs2234693 and rs9340799 in ESR1 have been largely studied.…”
Section: Discussionmentioning
confidence: 61%
“…The genetic polymorphisms rs2234693 and rs9340799 in ESR1 have been largely studied. The evidence linking these polymorphisms and its haplotype to bone mineral density (28,46). Also they were associated with postmenopausal osteoporosis (28,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mondockova et al had found that rs9340799 polymorphism may contribute to decreased BMD in postmenopausal women in southern Slovakia [14]. Nevertheless, Wang et al had showed that rs2234693 polymorphism but not rs9340799 was associated with PMO [21].…”
Section: Discussionmentioning
confidence: 99%